Numerical modelling of photocurrent for CuInxGa1-xSe2-based bifacial photovoltaic cell - Bouchekouf, Seloua; Guentri, Hocine; Hassinet, Liamena; Merzougui, Amina; Kebaili, Farida (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Research on thin-film solar cells based on CuInSe2 has demonstrated the potential of this compound for photovoltaic conversion. The introduction of gallium as a substitute for indium has led to the creation of the CuInxGa1-xSe2 (CIGS) structure, which could serve as one of the foundational materials for high-performance solar cells. This paper focuses on modelling the bifacial back surface field (BSF) solar cell. We took the CdS/CIGS thin-film structure as an application example to optimize, through simulation, the physical-electronic and geometric parameters of the various layers of the cell. Our study has led us to interesting results that clearly show that the performance of the cell is precisely controlled by the space charge region associated with the CIGS absorber layer, which is promising for research in photovoltaics due to its high absorption coefficient and the ability to vary its bandgap, allowing for increased conversion efficiency. The high-doped P+ layer (Wbsf) enhances the total photocurrent of the bifacial.